Mythical guardians to modern advocates: Rewriting Mbok Delima, a guardian of food sovereignty in ASEAN context - Ambarwati, Ari; Siswiyanti, Frida; Muttaqin, Khoirul (Universitas Ahmad Dahlan, 2025)
Reframing Mbok Delima in the Osing-Javanese folktale Panji Gimawang through a Gender Equality and Social Inclusion (GESI) lens, this study reveals her obscured expertise in agriculture and food security and challenges the patriarchal bias of traditional storytelling. Using Todorov’s narrative sequence, equilibrium, disruption, recognition, repair, and new equilibrium, The researcher demonstrates how Mbok Delima can be repositioned as the primary agent safeguarding food sovereignty. We propose a portable rewriting framework that blends gender analysis, social-inclusion metrics, and pedagogical strategies. Although rooted in a Javanese case, the framework is transferable across Southeast Asia: comparable agrarian heroines such as Mae Posop (Thailand), can likewise be reinterpreted to amplify women’s roles in local food systems. By aligning with ASEAN principles of respect, peace, prosperity, diversity, and human-rights protection, as well as the ASEAN Integrated Food Security Framework 2025, this study positions folktale revision as a regional strategy for promoting progressive gender dynamics, inclusive cultural discourse, and resilient food security.